Purple urine bag syndrome: an unusual clinical presentation - Rajakumar, Rontgen; Khan, Nida; Mahadik, Abhishek (International Journal of Research in Medical Sciences, 2020)
Purple Urine Bag Syndrome (PUBS) is a rare presentation of urinary tract infection caused by certain bacteria that produce sulphatases and phosphatases that bring about metabolism of tryptophan, leading to production of pigments indigo and indirubin that together impart purple colour of urine. It is a benign condition, most often associated with long term urinary catheterization, renal diseases, chronic constipation and female gender. Commonly implicated organisms include Proteus mirabilis, Klebsiella pneumoniae, Providencia stuartii. Diagnosis is made on urinary culture. Treatment includes reassurance and antibiotics for UTI. We present a case of purple urinary bag syndrome in a female patient of carcinoma stomach presenting with gastric outlet obstruction.